2014
DOI: 10.1371/journal.pone.0105414
|View full text |Cite
|
Sign up to set email alerts
|

Elevated Levels of Dickkopf-1 Are Associated with β-Catenin Accumulation and Poor Prognosis in Patients with Chondrosarcoma

Abstract: BackgroundDickkopf-1 (DKK1) is an antagonist of Wnt/β-catenin signaling implicated in tumorigenesis. However, the biological role of DKK1 and β-catenin involved in chondrosarcoma has not been sufficiently investigated. This study was designed to investigate the expression profiles of DKK1 and β-catenin, and to clarify their clinical values in chondrosarcoma.MethodsThe mRNA and protein levels of DKK1 and β-catenin in fresh chondrosarcoma and the corresponding non-tumor tissues were analyzed by Real-time PCR and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 29 publications
(29 citation statements)
references
References 35 publications
(69 reference statements)
2
26
1
Order By: Relevance
“…In accordance with our survey, Chen et al (23) reported that both DKK-1 and b-catenin levels were in high level in chondrosarcoma when compared with nontumor tissues. Furthermore, DKK-1 and b-catenin levels were remarkably linked to overall survival.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In accordance with our survey, Chen et al (23) reported that both DKK-1 and b-catenin levels were in high level in chondrosarcoma when compared with nontumor tissues. Furthermore, DKK-1 and b-catenin levels were remarkably linked to overall survival.…”
Section: Discussionsupporting
confidence: 92%
“…Furthermore, DKK‐1 and β‐catenin levels were remarkably linked to overall survival. The association of increased DKK‐1 levels with β‐catenin accumulation has been indicated in chondrosarcoma, and its expression was correlated with poor prognosis in patients with chondrosarcoma .…”
Section: Discussionmentioning
confidence: 98%
“…Detailed experimental procedures for immunohistochemistry have been described previously. [29][30][31] Briefly, after antigen retrieval, PRMT1 (ab73246; 1:200; Abcam) and YAP (ab39361; 1:100; Abcam) immunoreactivities were detected using the EnVision+, Peroxidase system (DAKO Diagnostics, Glostrup, Denmark). The slides were developed with DAB (diaminobenzidine) substrate (DAKO Diagnostics) and counterstained with hematoxylin.…”
Section: Immunohistochemistry and Evaluation Of Stainingmentioning
confidence: 99%
“…In support of this, DKK1 positivity has been associated with lymph node metastasis in cancers (Kemik et al , ; Li et al , ; Shi et al , ; Shi et al , ; ). DKK1 staining in tumours has also been co‐detected with β‐catenin, and in some instances, patients with dual staining had a worse prognosis, including decreased overall survival (Yu et al , ; Xu et al , ; Chen et al , , ; Shi et al , , ). It is puzzling that DKK1, an inhibitor of β‐catenin‐dependent Wnt signalling, is detected in tumours with β‐catenin, an indicator of activated Wnt/β‐catenin signalling.…”
Section: Dkk1 Overexpression In Cancermentioning
confidence: 99%